Peran Agama Dan Moderasi Beragama dalam Membentuk Perilaku Ramah Pendatang: Bukti Empiris Pada 5 Negara Asean - Askar Muhammad; Fithra Faisal Hastiadi (Asyafina Akademik Press, 2022)
Under the ASEAN framework, Southeast Asia is increasingly integrated. Freedom of mobility among ASEAN member countries is one of the implications of the expansion of intra-regional trade in ASEAN. In addition, differences in living standards and wages are also one of the attractions of mobility between regions. In the midst of these developments, negative sentiment towards foreigners is inevitable. Facing this reality, this study tries to see how the pattern of sentiment towards immigrants is formed in the ASEAN region. Is the ASEAN community basically ready to accept the wave of foreign arrivals? This study, using 12,112 respondents from 5 ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, and the Philippines) taken from the 6th and 7th World Value Survey waves, found that religious factors significantly reduced negative sentiment towards immigrants. On the other hand, it was also found that globalization has different impacts on sentiment patterns depending on which aspect of a country is globalized.